Asymmetric approach towards the total synthesis of (+)-actinopyllic acid. Issue 15 (13th April 2017) - Xue, Fei; Xiao, Tao; Li, Min; Zhang, Kai-Fang; He, Li-Ping; Qin, Yong; Liu, Xiao-Yu; Zhang, Dan
Abstract: This paper describes our efforts towards the asymmetric total synthesis of (+)-actinophyllic acid. Starting from the chiral oxazolidinone9, an azocino [4, 3- b ]indolyl intermediate (5 ) possessing the A/B/C ring system and the C16 quaternary stereogenic center of actinophyllic acid has been synthesized. Key steps include a LHMDS-promoted condensation to establish the critical C2–C16 bond and a successive four-step transformation to assemble the eight-membered C-ring of the target molecule. Graphical abstract: